MENGHADIRKAN KEBERAGAMAN DALAM KELAS: ANALISIS LITERATUR TENTANG INKLUSI SISWA DENGAN KEBUTUHAN KHUSUS - Naheria; Loso Judijanto; Rossa Ramadhona; Nana Citrawati Lestari; Muhammad Sukron Fauzi (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
The purpose of this study was to explore various strategies and best practices in creating an inclusive learning environment for students with special needs. This study also aims to identify challenges faced by educators in implementing inclusive education and provide recommendations to improve teacher training and support. This study is a literature study. Literature study is the collection of information from various published written sources to gain a better understanding of the topic being studied. This includes critical analysis and synthesis of previous findings. The results of this study indicate that inclusion in education is a practice that ensures all students, including those with special needs, have the opportunity to learn in a regular classroom environment. This concept is rooted in the right of every individual to receive a quality education, which supports students' social and emotional development through interaction with peers. Inclusion also offers academic benefits, providing students with special needs with access to diverse teaching methods and more complete resources, which improves their learning outcomes. However, the success of inclusion depends on teacher training, policy support, and collaboration between parents, schools, and communities, creating an environment that values ??diversity and prepares students to contribute to a more inclusive society.